2013
DOI: 10.5808/gi.2013.11.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Genome Study for Anaplastic Thyroid Cancer

Abstract: Anaplastic thyroid cancer (ATC) belongs to the most malignant and rapidly progressive human thyroid cancers and its prognosis is very poor. Also, it shows high resistance to cancer treatments, so that effective treatment for ATC has not been found to date, and virtually all patients terminate their life rapidly after diagnosis. Although targeted treatment of genetic alterations has emerged as an extremely promising approach to human cancers, such as BRAF in metastatic melanoma, it remains unclear that how comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
(77 reference statements)
0
21
0
1
Order By: Relevance
“…A review of the molecular studies on thyroid cancer demonstrated that the Ras/Raf/mitogen-activated protein kinase kinase̸extracellular signal-regulated kinase (also referred to as mitogen-activated protein kinase; MAPK) and the phosphoinositide 3-kinase (PI3K)/Akt signaling pathways are key to the development and progression of thyroid cancer, which are associated with tumorigenesis, proliferation, apoptosis, angiogenesis, metastasis and metabolism (2,5,10,11). The MAPK signaling pathway involves a series of serine/threonine protein kinases that convert extracellular stimuli into a wide range of cellular responses through transmembrane protein receptors, such as epidermal growth factor receptor/vascular endothelial growth factor (VEGF)/rearranged during transfection (RET) (12,13).…”
Section: Development and Progression Of Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the molecular studies on thyroid cancer demonstrated that the Ras/Raf/mitogen-activated protein kinase kinase̸extracellular signal-regulated kinase (also referred to as mitogen-activated protein kinase; MAPK) and the phosphoinositide 3-kinase (PI3K)/Akt signaling pathways are key to the development and progression of thyroid cancer, which are associated with tumorigenesis, proliferation, apoptosis, angiogenesis, metastasis and metabolism (2,5,10,11). The MAPK signaling pathway involves a series of serine/threonine protein kinases that convert extracellular stimuli into a wide range of cellular responses through transmembrane protein receptors, such as epidermal growth factor receptor/vascular endothelial growth factor (VEGF)/rearranged during transfection (RET) (12,13).…”
Section: Development and Progression Of Thyroid Cancermentioning
confidence: 99%
“…Thyroid cancer includes differentiated thyroid cancer (DTC), poorly differentiated and undifferentiated thyroid cancer. Papillary thyroid cancer (PTC), accounting for 80-85% and follicular thyroid cancer (FTC), accounting for 10-25% of the cases, are the most common subtypes of DTC, with Hürthle cell thyroid cancer, originating from thyroid follicular cells, accounting for 1-2% of DTCs (2). Anaplastic thyroid cancer (ATC), accounting for ~1.7% of the cases, is a subtype of thyroid cancer that develops from DTC, which has lost its iodine uptake ability, has become highly aggressive and is associated with a poor prognosis, with a median survival of ~5 months and an 1-year survival rate of 20% (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…34 Limited epigenetic studies looking at microRNA and promoter methylation have also been performed on ATC tumors with some promise, but they are yet to come to the forefront as potent diagnostic markers. 28 ATCs are typified by hits to multiple signal transduction and cell cycle pathways (Table 1) such as TP53, PTEN-PI3K/ AKT, RAS/RAF/MAPK, and Wnt/β-catenin ( Figure 2A). Mutations in RAS (N-or H-) and BRAF which are also present in PTC suggest that they could be early oncogenic events, compounded by those in TP53, PI3K, and β-catenin resulting in progression to the aggressive dedifferentiated ATC phenotype.…”
Section: Genetics Of Atcmentioning
confidence: 99%
“…[24][25][26] Multiple studies using arrayCGH (array comparative genomic hybridization) has shown that besides copy number changes, 8,27 chromosomal gains and losses as well as gene rearrangements involving the RET proto-oncogene are also present in ATC. 28 In an attempt to identify novel markers or therapeutic targets, immunohistochemistry as a tool has been used extensively to evaluate loss or overexpression of various signaling molecules.…”
Section: Genetics Of Atcmentioning
confidence: 99%
See 1 more Smart Citation